THE COMPARATIVE STUDY OF THE CYCLICITY AND RHYTHMICITY IN PRECAMBRIAN SEQUENCES - Negrutsa V.Z. (My University, 1998)
Results of the study of the cyclicity and rhythmicity in Precambrian sequences, i.e., of periodicity in the development of sedimentation basins, magmatism, folding, and metamorphism, are discussed. Cycles and rhythms in the formation of Precambrian rocks are compared with similar Phanerozoic cycles and rhythms. The original cause and interrelated pulsatory development of external and internal geospheres during the entire history of the earth are considered. It is shown that principles of Phanerozoic stratigraphy can be applied in the Precambrian stratigraphy and stratigraphic subdivision of particular Precambrian sections may be performed as thoroughly and reliably as that of Phanerozoic sections. It is emphasized that the level of detailedness in stratigraphic subdivision of the Precambrian and Phanerozoic sections corresponds to the state of knowledge about the Precambrian and Phanerozoic evolution of the earth. The further improvement of a general model of periodicity in geological evolution is assumed to be dependent on the study of development stages of the Precambrian sedimentary basins.
Keywords: Precambrian; Precambrian; Докембрий